Digitalising the Clearance Processes of Higher Education Institutions through the Design and Implementation of an Online Clearance System - Essel, Daniel Danso; Techie-Menson, Henry; Oppong, Stephen Opoku; Alakuu, Augustine (International Journal of Scientific Research and Management (IJSRM), 2023)
Students in Higher Education Institutions (HEIs) are expected to participate in a number of important activities throughout their time in school including clearance before graduation. Clearance serves as a means of ensuring graduating students satisfy all required administrative criteria. Both students and clearing officers face a daunting task as a result of the present manual clearance procedures in most HEIs. The development of this online student’s clearance system (UEW-SOCS) was done using the agile methodology. The languages and technologies used are ASP.NET MVC 5, MSSQL 2014 and JavaScript, HTML and CSS.  The result is an effective and efficient web-based application that overcomes the challenges of manual paper-based systems characterized by mundane tasks by providing a responsive interface with role-based access to ensure high security. Ultimately, this study designed and implemented a successful and effective online clearance system for Higher Education Institutions that could be a critical decision support system.